1021. HIV-1 RNA Blips and Low-Level Replication During Phase III/IIIb Cabotegravir + Rilpivirine Long-Acting Studies Are Similar to Oral 3-Drug Therapy and Not Associated with Week 48 Virologic Outcome. (31st December 2020) - Talarico, Christine L; Wu, Sterling; Upadhyay, Ojesh R; Clair, Marty St; Van Eygen, Veerle; Hudson, Krischan J; Griffith, Sandy; Harrington, Conn M; van Lunzen, Jan; Margolis, David; Spreen, William
Abstract: Background: Phase III/IIIb studies demonstrated cabotegravir (CAB) + rilpivirine (RPV) long-acting (LA) dosed every 4 weeks (Q4W) was noninferior to current antiviral regimen (CAR) (FLAIR and ATLAS) and CAB + RPV LA dosed every 8 weeks (Q8W) was noninferior to Q4W (ATLAS-2M) through Week 48 (W48). HIV-1 ribonucleic acid (RNA) blips (viral load [VL] ≥50 to < 200 c/mL) are common during antiretroviral therapy (ART) and generally not associated with subsequent virologic failure (2 consecutive HIV-1 RNA ≥200 c/mL). We compared the frequency of HIV-1 RNA blips and low-level qualitative and quantitative HIV-1 RNA replication among participants treated with CAB+RPV LA and oral CAR and assessed impact on virologic outcome. Methods: Plasma samples collected at study visits were analyzed for HIV-1 RNA viral load using the Abbott RealTime HIV-1 assay and qualitative target detected (TD) or target not detected (TND) outcomes were provided for HIV-1 RNA < 40 c/mL. The HIV-1 SuperLow assay (bioMONTR Labs) was used to measure HIV-1 RNA < 2 c/mL at Baseline and W48. Results: The proportion of participants with HIV-1 RNA blips was similar overall between Q4W CAB + RPV LA and CAR arms in FLAIR (38/283 [13%] vs 39/283 [14%]) and ATLAS (17/308 [6%] vs 23/308 [7%]). Presence of HIV-1 RNA blips in either arm was not associated with virologic non-response at W48 (HIV-1 RNA ≥50 c/mL per US Food and Drug Administration Snapshot). In ATLAS-2M, HIV-1 RNA blips were observed in 32/523 (6%; Q4W) and 18/522 (3%; Q8W) of participants, with W48 virologic nonresponse in 2 Q4W and 0 Q8W participants. TD outcomes at individual study visits were comparable between study arms for the 3 studies. At W48, the proportion of participants with HIV-1 RNA < 2 c/mL was similar to Baseline and similar between treatment groups in all studies. Conclusion: The proportions of study participants with HIV-1 RNA blips, TD viral load results, and HIV-1 < 2 c/mL were similar between the Q4W and Q8W CAB+RPV LA and the oral 3-drug CAR arms through W48 in phase III/IIIb studies. HIV-1 RNA blips did not predict virologic nonresponse (Snapshot analysis) at W48. Disclosures: Christine L. Talarico, M.S, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Sterling Wu, PhD, GlaxoSmithKline (Employee, Shareholder) Marty St. Clair, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Veerle Van Eygen, MSc, Janssen Pharmaceutica NV (Employee) Krischan J. Hudson, PhD, MPH, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Sandy Griffith, PharmD, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Conn M. Harrington, BA, ViiV Healthcare (Employee) Jan van Lunzen, MD, PhD, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) David Margolis, MD, MPH, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) William Spreen, PharmD, ViiV Healthcare (Employee, Shareholder)